2020
DOI: 10.29261/pakvetj/2019.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Seed Extract on Tibial Dyschondroplasia Incidence, Liver Weight, and Tibial Angiogenesis in Chickens

Abstract: Among avian metabolic disorders, Tibial dyschondroplasia (TD) has a wide prevalence worldwide in chickens that are identified by non-mineralization and avascularization of the growth plate (GP). Grape seed extract (GSE) reduces the inflammation and oxidative stress by scavenging free oxygen specie and has some anti-cancer and angiogenic activity. This study was carried out to evaluate the role of GSE for the therapy of the chickens affected with TD. Arbor Acres broiler chicks (n=240) weighing 47±6g were fed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 59 , 60 Whereas, grape seed extract, a great source of resveratrol has been also declared to possess the antioxidant and anti-inflammatory effects. 61 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 , 60 Whereas, grape seed extract, a great source of resveratrol has been also declared to possess the antioxidant and anti-inflammatory effects. 61 …”
Section: Resultsmentioning
confidence: 99%
“…59,60 Whereas, grape seed extract, a great source of resveratrol has been also declared to possess the antioxidant and anti-inflammatory effects. 61 This evidently relates the fact that how these natural compounds can help to ameliorate the metabolic impairment which are the key factors associated with prevalence and worsening of metabolic disorders. 62 Additionally, the outcomes of histological inspection of pancreas and intestine in our study were found to be in accordance with biochemical effects observed during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress induces the release of Cyt-c from the mitochondria that is the key factor of apoptosis, while the antioxidant enzyme Gpx4 can eliminate lipid peroxides in the mitochondria to inhibit the production of Cyt-c and reduce apoptosis (73). DQ can also affect the caspase signal pathway by inducing oxidative stress to produce ROS and enhance the activities of caspase-3 and caspase-9 in the liver tissue (74)(75)(76)(77)(78). It is found that there is a relationship between Bax/Bcl-2 and caspase.…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria species affect intestine of the bird and cause bloody diarrhea, poor Feed Conversion Ratio (FCR) and mortality which lead to heavy economic losses to poultry industry (Chapman, 2014;Shahid et al, 2020;Khater et al, 2020). The coccidiosis infection starts with the ingestion of sporulated oocysts by the chicken from contaminated feed and water (Qamar et al, 2020;Zhang et al, 2020). Coccidian oocysts produce millions of oocysts by asexual and sexual multiplication within the host.…”
Section: Introductionmentioning
confidence: 99%